Characterization of an instrumented GeoStrap® with plastic optical fiber bragg gratings - Aressy, Matthieu; Bennani, Yassine; Lacraz, Amédéé; Kalli, Kyriacos (My University, 2018)
Polymer Optical Fibres (POF) sensors have attracted significant interest in the field of earthwork structure monitoring mainly due to their high elongation capability in contrast to traditional glass optical fibres (GOF). Recent development in the POF field have shown that it is now possible to inscribe fibre Bragg gratings (FBGs) in low loss perfluorinated POF (POFBG). The perfluorinated fibres, such as CYTOP, have losses in the near infrared, at 1550nm that are approximately 0.2dB/m. CYTOP is extremely transparent as it exhibits low scattering loss due to its highly amorphous nature and low optical absorption because of the perfluorinated backbone that shift the optical losses to the infrared, at 7.7–10μm. However, it is precisely this improved loss performance that hinders the laser inscription of basic optical components such as FBGs in CYTOP; in contrast PMMA has an absorption feature that peaks at close to 325nm, which enables laser-induced material modifications using a HeCd laser. The excellent transparency of CYTOP makes it suitable for use with femtosecond laser direct write methods. We inscribe a complex FBG sensor array in CYTOP fibre and show that this robust and smart sensing strand is compatible with coating methods that are used in the geosynthetic industry. This new development extends the possibility of instrumentation from distributed strain measurements alone to potential local load, strain, temperature or pressure measurements. In this paper, the authors will present the manufacturing process of an instrumented GeoStrap® and the associated characterization using standard geosynthetic testing such as tensile test and pull-out test. The results obtained will be discussed and the prospects presented. © 2018 11th International Conference on Geosynthetics 2018, ICG 2018. All rights reserved.
Keywords: FBG; Geosynthetic; Optical sensor; POF; Pull-out; Tensile